El hogar como espacio simbólico en los poemarios Matar a un conejo y Llévame a casa, por favor de la autora Andrea Rojas Vásquez, - Correa Cruz, Magneli del Rosario (2023)
This thesis presents a critical review of the construction of home as a symbolic space in the poetry books "Matar a un conejo" and "Llévame a casa, por favor" by the author Andrea Rojas Vásquez. The objective is to characterize the home that the speaker escapes from in its search for symbolic homes and to identify the body as one of the manifestations of pleasure that contribute to the creation of symbolic spaces in the poetry collections mentioned above. This research used a qualitative approach and a descriptive design. Findings show that the home in which the poetic voice resides is a place characterized by poverty, abandonment, and the absence of a complete family. In the midst of this fragmented home from which the poetic voice flees, an imaginary home is created, which turns it into a symbolic space. Furthermore, the body is found to be a source of pleasure for the speaker, nevertheless this body does not belong to her. Finally, in addition to finding pleasure in her body and literature, it can be concluded that the female figure depicted in the poems lacks individual sovereignty over her own body, which leads her to imagine that her body is a symbolic space of security and serenity. Keywords: Home, symbolic space, pleasure, body.